efectuati:(-13/6)+5/6;(-7/4)+(-3/4);(-7/6)+-1/6)
Răspunsuri la întrebare
Răspuns de
1
Răspuns:
Explicație pas cu pas:
(-13/6)+5/6;(-7/4)+(-3/4);(-7/6)+(-1/6)
=-13/6 - 5/6*4/7 + 3/4*6/7 - 1/6
= -14/6 - 20/42 + 18/28
= -7/3 - 10/21 + 9/14
= -7/3 - 20/42 + 27/42
= -7/3 + 7/42
= -7/3 + 1/6 = -14/6 + 1/6 = -13/6
Alte întrebări interesante
Engleza,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă